Troubleshooting and maintenance of high-performance liquid chromatography during herbicide analysis: an overview - Tayeb, M.A.; Ismail, B.S.; Khairiatul-Mardiana, J.; Goh, Choo Ta (Universiti Kebangsaan Malaysia, 2016)
Glufosinate ammonium or ammonium salt (ammonium-(2RS)-2-amino-4- (methylphosphinato) butyric acid; C5 H15N2 O4 P) is a commonly used polar herbicide in Malaysia and present in a variety of environmental waters at the sub-ppb level. Thus, glufosinate ammonium is analyzed in soil and water using high-performance liquid chromatography (HPLC), which is a complex yet the most powerful analysis tool. HPLC is tremendously sensitive and highly automated and HPLC instrumentation and machinery have improved over the years. However, typical problems are still encountered. HPLC users and advanced learners require help in identifying, separating and correcting typical problems. All HPLC systems consist of similar basic components. Although it is a modular system, trouble can occur in each component and change the overall performance. Resolving these problems may be expensive. This review describes the different aspects of HPLC, particularly troubleshooting, common problems and easy guidelines for maintenance.